Where, When, and By Whom: An Exploratory Analysis of COVID-19 Public Health Violations. (November 2021) - Leal, Wanda E.; Kurland, Justin; Piquero, Alex R.; Gloyd, Elizabeth L.; Leeper Piquero, Nicole
COVID-19 health restrictions not only affected crime rates but also created a new and temporary type of crime, COVID-19 public health violations. Unfortunately, this new crime type has not yet been empirically scrutinized. The current study is the first to explore these COVID-19 public health violations by using a dataset created by the City of San Antonio which documents all calls and inspections about COVID-19 public health violations. Specifically, this study investigates the location types (where) that produce the greatest number of calls/inspections, warnings, and citations for COVID-19 public health violations; how they trended over time (when); and which agencies responded to and enforced them (who). The results indicate that there were differences across location type, variation throughout the observation period, and violations were enforced by several agencies. It is crucial to document the effect of COVID-19-related policies so that we may be better prepared for the future.